FIQH REGULATIONS FOR NATURAL DISASTERS: METHODS OF PERFORMING PRAYER IN CRITICAL SITUATIONS (SALAM Digest: Syariah and Law Undergraduate Symposium, 2023)
Natural disasters, occurring in various forms such as earthquakes, hurricanes, floods, and tornadoes, have repeatedly placed people in critical situations, often resulting in loss of life, possessions, and homes. Every natural phenomenon is decreed by Allah SWT to occur within divine wisdom. Despite the struggles faced during such crises, Muslims are obligated to continue performing prayers, as it is a fundamental pillar of Islam. However, Allah SWT, in His mercy, has provided rukhsah (concessions) for those experiencing hardship. According to the Islamic Legal Maxim Al-Masyaqqah Tajlibu Al-Taisir (“Hardship begets Facility”), difficulty serves as a basis for easing obligations, allowing Shariah to be adapted through leniency and lightening requirements in challenging situations. Islam has therefore established specific regulations and guidelines for performing prayer under duress. This research, in the context of Fiqh Disaster, focuses on the application of ablution, tayammum, and al-jabirah, as well as the practice of combining prayers (jamak) under conditions of masyaqqah (hardship). This study acknowledges the practical challenges individuals face during natural disasters and explores how Islamic jurisprudence provides accommodations to ensure religious obligations can still be fulfilled. It highlights the adaptability of Islamic teachings to real-life situations, emphasizing compassion and understanding in the face of adversity.